Problem and Constraints Faced by Rural Scheduled Caste Women for Entrepreneurship - Sachan, Divya; Sethi, Nishi (International Journal of Bio-resource and Stress Management, 2019)
Entrepreneur is a key factor of entrepreneurship. It is responsible for shaping the economy and they help in creation of new wealth and new jobs by inventing new products, process and services. In present time, female entrepreneurship is gaining attention and importance in light of the evidence of the importance of new business creation for economic growth and development. This paper attempts to the constraints encountered by scheduled caste women to start cutting and tailoring as an enterprise and decision-making pattern of scheduled caste women to start cutting and tailoring as an enterprise. The study was conducted in Hisar District of Haryana state, India during the year 2016. The sample comprised of interested 120 SCs rural women from purposively selected ten villages of four blocks (Hisar I, Hisar II, Barwala, Hansi rural) of Hisar district, Haryana state. Six days training through experts was imparted to the women on garment construction. To assess the problem and constraints faced by the SC women for entrepreneurship, a well structured interview scheduled was subjected after imparting training to respondents. It was found that the main constraints of the respondents were economic dependency and marketing challenges, as far as decision making is concern, decisions regarding technical aspect were mainly taken by the respondent but other major decisions were male dominated.